Studi Epidemiologi dan Gambaran Program Eliminasi Filariasis Limfatik di Kabupaten Bogor - Muhammad Nirwan; Upik Kesumawati Hadi; Susi Soviana; Surachmi Setyaningsih; Fadjar Satrija (Loka Litbang Kesehatan Pangandaran, 2020)
Abstract. Filariasis is still a health problem in Bogor Regency. The discovery of filariasis sufferers has growing during the year since 2004 until now with a total of 117 people. The mass prevention drug administration program (POPM) has been implemented since 2015. This study aims to identify the epidemiological distribution of clinical filariasis sufferers and an overview of the achievement of filariasis elimination program in Bogor district. The research using descriptive design with a quantitative approach. The data in this study used secondary data from Bogor District Health Office and Bogor Central Bureau of Statistics. Data were analyzed descriptively and identify differences and relationships between variables used the chi-square test. The results of the study showed the epidemiological distribution of filariasis in Bogor Regency with predominantly female patients (59.8%) and productive age (36-45 years). The results from chi-square test showed that there was a significant difference between the age groups and theincidence of filariasis from year to year with a P value (0.000) <0.05, while the relationship between sex and the incidence of filariasis from year to year did not show a significant difference with the P value ( 0.07)>0.05. The spread of filariasis tends to fluctuate and continues to increase (75%). The results of the relationship test showed that there was no significant relationship between the number of cases and the level of family welfare with a P value (0.279)>0.05. The implementation of POPM, both treatment outcomes and treatment success rates, has exceeded the national target. Abstrak. Filariasis masih merupakan masalah kesehatan di Kabupaten Bogor. Penemuan penderita filariasis terus berkembang dari tahun ke tahun sejak tahun 2004 hingga sekarang dengan jumlah penderita sebesar 117 orang. Program pemberian obat pencegahan massal (POPM) telah dilaksanakan sejak tahun 2015. Penelitian ini bertujuan untuk untuk mengidentifikasi sebaran epidemiologi penderita filariasis klinis serta gambaran pencapaian program eliminasi filariasis di kabupaten Bogor. Desain penelitian adalah deskriptif dengan pendekatan kuantitatif. Data dalam penelitian ini menggunakan data sekunder dari dinas kesehatan Kabupaten Bogor dan Badan Pusat Statistik Kabupaten Bogor. Data dianalisis secara deskriptif dan untuk melihat perbedaan dan hubungan antar variabel digunakan uji chisquare. Hasil studi menunjukkan sebaran epidemiologi filariasis di Kabupaten Bogor dengan penderita dominan pada perempuan (59,8%) dan umur produktif (36-45 tahun). Hasil uji chi-square menunjukkan ada perbedaan signifikan antara kelompok umur dengan kejadian Filariasis dari tahun ke tahun dengan P value (0,000) < 0,05, sedangkan hubungan antara jenis kelamin dan kejadian Filariasis dari tahun ke tahun tidak menunjukkan perbedaan signifikan dengan P value (0,07) > 0,05. Penyebaran filariasis cenderung fluktuatif dan terus bertambah wilayahnya (75%). Hasil uji hubungan menunjukkan tidak ada hubungan signifikan antara jumlah kasus dengan tingkat kesejahteraan keluarga dengan P value (0,279) > 0,05. Pelaksanaan POPM baik angka capaian pengobatan dan angka keberhasilan pengobatan sudah melebihi dari target nasional.